Investigating the links between cultural values and belief in conspiracy theories: The key roles of collectivism and masculinity. - • Adam‐Troian, J., Wagner‐Egger, P., Motyl, M., Arciszewski, T., Imhoff, R., Zimmer, F., ... & van Prooijen, J. W (Wiley on behalf of the International Society of Political Psychology, 2020)
Recent research suggests that adherence to conspiracy theories (CT) stems from basic psychological mechanisms and is linked with other belief systems (e.g. religious beliefs, Newheiser et al., 2011). Studies so far have focused on individual difference variables. We wanted to test whether culture predicts CT prevalence from a situated cultural cognition perspective (Oyserman, 2016). Using Hofstede’s (1984) model of cultural values, two exploratory nation-level analyses of data from 19 and 18 countries using different measures of CT (Study 1a, N = 12,255; Study 1b, N = 30,994) revealed positive influence of Masculinity and Collectivism on CT. A confirmatory cross-sectional study replicated these findings among US citizens (Study 2, N = 350) using individual-level measures of Hofstede’s values. These results suggest for the first time that culture might be related to the cognitive processes at work behind CT. They open the way to novel theoretical and applied research avenues.
Keywords: conspiracist beliefs, cultural values, situated cognition, 9/11 attacks, cross-cultural